The Impact of Chest Computed Tomography in A Covid-19 Reference Hospital - First Wave - Distrito Federal - Brazil - Dias De Souza Gleim; Rodrigues Queiroz De Souza Luciana; Gomes De Souza Gabriela; Queiroz Souza Thales; Rodrigues Castro Ulysses; Guimaraes Ibiapina Adriano; Henrique Ramos Feitosa Paulo; Aron Ajzen Sérgio (International Journal of Coronaviruses, 2022)
Objectives To evaluate the diagnostic accuracy of chest CT for the diagnosis of COVID-19 associated with the clinical presentation and in relation to the PCR-RT. Sensitivity, specificity, positive predictive value and negative predictive value, gender, age group and degree of lung involvement will be evaluated. Methods We evaluated 1545 patients with chest CT, delineating the age range and degree of lung involvement, and 306 patients with chest CT and PCR-RT. Results Of the 1545 examinations, 53% were men and 47% were women, there was greater involvement in the 50-59 age group. In the pulmonary study, 55.05% were COVID-19. In the degree of lung involvement 37.70% were mild, 35.76% were moderate, and 26.54% were severe. In the distribution by age, there was a greater involvement between 50-59 years with 56% between moderate (27.6%) and severe (28.0%). Between tomography and PCR-RT, the sensitivity was 68.8%, specificity 59.5%, accuracy 91.3%, with prevalence 31.9%, positive predictive value 44.3% and negative predictive value 80.3%, in females, sensitivity 55.3%, positive predictive value 37.1%, negative predictive value 75.3%, in males, sensitivity 81.6%, positive predictive value 50, 6 and negative predictive value 86.6%.The sensitivities are different between the genders with p of 0.005 and specificity of 0.938, with age effect, starting at 45 years we have a p of 0.057 that decreases to 0.006 at 80 years for sensitivity and specificity. Conclusions The sensitivity and accuracy of CT scan in relation to PCR-RT was significant. Sensitivity increases with prevalence and in the older age group and in men.
Keywords: Computed tomography